Deconstructing the International Business Cycle : Why does a U.S. sneeze give the rest of the world a cold? (IMF Working Papers; Working Paper ;, 2010)
The 2008 crisis underscored the interconnectedness of the international business cycle, with U.S. shocks leading to the largest global slowdown since the 1930s. We estimate spillover effects across major advanced country regions in a structural VAR (SVAR) using pre-crisis data. Our new method freely estimates the contemporaneous correlation matrix for underlying shocks in the VAR and (uniquely, to our knowledge) the associated uncertainty. Our results suggest that the international business cycle is largely driven by U.S. financial shocks with a significant impact from global shocks, mainly reflecting commodity prices. Other advanced economic regions play a much smaller and regional role in growth spillovers. Our findings are consistent with the emerging evidence on the current crisis.